The Effects of Leverage, Solvency, Company Status, and Company Age on Voluntary Disclosure of Annual Reports of IDXV30 Issuers on the Indonesia Stock Exchange (IDX) for the 2021–2023 Period - Dinda Lestari; Sri Rahayu; Fitrini Mansur (International Forum of Researchers and Lecturers, 2025)
This study aims to identify the effect of leverage, solvency, company status, and company age on voluntary disclosure in the annual reports of IDXV30 issuers listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. The independent variables used are leverage, solvency, company status, and company age. The dependent variable in this study is voluntary disclosure. This study uses a quantitative approach. This study focuses on the population of IDXV30 issuers listed on the Indonesia Stock Exchange in the period 2021-2023. This study uses a purposive sampling method with a total sample of 16 companies. Data analysis in this study was conducted using multiple linear regression techniques, which were operated with the IBM SPSS version 26 program. The results of this study indicate that partially, leverage and solvency have an effect on voluntary disclosure. Partially, company status and company age do not have an effect on voluntary disclosure. Simultaneously, leverage, solvency, company status, and company age influence voluntary disclosure.